Endothelial, renal and hepatic variables in wistar rats treated with Vancomycin - BRUNIERA,FELIPE R. (2014)
Vancomycin (VCM) is indicated in combat against Gram-positive infections, but it is not considered a first-choice drug because of its adverse effects. It is believed that oxidative stress is the primary mechanism of endothelial injury and the consequent VCM toxicity, which varies from phlebitis to nephrotoxicity. Moreover, dose recommendations, dilution, rates and types of infusion are still controversial. The aim of this study was to determine the effect of different VCM dilutions in endothelial, liver and kidney injuries by biochemical parameters and histopathological analysis. Wistar rats were randomly divided into six groups and subjected to femoral vein cannulation for drug administration. Control groups received 0.9 ml of saline and the others received VCM (10mg/Kg/day) at dilutions of 5.0 and 10.0 mg/mL for 3 and 7 days. Homocysteine, hs-CRP, AST, ALT, GGT, urea, creatinine, lycopene, alpha-tocopherol, beta-carotene and retinol were analyzed. Kidney, liver and cannulated femoral vein fragments were collected.This study showed alterations in ALT which featured hepatotoxicity. However, drug dilutions were not able to show changes in other biochemical parameters. In contrast, kidney and endothelium pathological changes were observed. More studies are needed to characterize VCM induced kidney and endothelium toxicity and biochemical markers able to show such morphological modifications.